Inovasi Pengelolaan Sampah (Studi tentang Inovasi Ir. Koderi pada Tempat Pembuangan Akhir (TPA) Talangagung-Kepanjen) - Sulistianto Amin Dai (Jurnal Administrasi Publik, 2016)
Abstract: The Innovation of Trash Management (Study about Innovation by Ir. Koderi at Final Dumping Site (TPA) of Talangagung-Kepanjen). In sustainable development concept, trash is only an issue within this concept that needs for review. Trash management process in Malang Regency is usually applying the concept of collect, transport and dump to Final Dumping Site (TPA). However, TPA can give a huge impact on environment. If trash at TPA is not processed properly, it may endanger the environment. Therefore, it is necessary to give a touch of innovation into trash management at TPA, especially the innovation by the Organizer of TPA Wisata Edukasi Talangagung-Kepanjen. The innovation suggested by Ir. Koderi at TPA Wisata Edukasi Talangagung-Kepanjen involves control, treatment and utilization of TPA biogas. After processed through purification system assembled by Mr. Koderi, the resultant biogas is distributed into immediate community. The appreciated social impact on the environment is that the toxic gases which endanger the environment such as H2S, CO2 and CH4 can be removed through purification system. However, the other dangerous effect from TPA biogas is the presence of alkali water at TPA Wisata Edukasi Talangagung-Kepanjen. Alkali water must be well processed to avoid environmental contamination. Favorable economic impact is that biogas may reduce the cost expended by the community in buying LPG because the community can obtain the needed gas directly from TPA distribution. Social impact can also be positive because a paradigm is possibly changing because the community who previously dislikes, or even hates, TPA, will change into liking the presence of TPA around them. Keywords: trash management, innovation, the impact of innovation Â  Abstrak: Kinerja Inovasi Pengelolaan Sampah (Studi tentang Inovasi Ir. Koderi pada Tempat Pembuangan Akhir (TPA) Talangagung-Kepanjen) Dalam konsep pembangunan berkelanjutan, sampah merupakan salah satu kajian didalamnya. Proses pengelolaan sampah di Kabupaten Malang pada umumnya adalah menggunakan konsep kumpul, angkut dan buang (TPA), di TPA inilah yang sangat berdampak terhadap lingkungan. Jika sampah di TPA tidak diolah dengan baik, maka akan sangat berbahaya bagi lingkungan. Oleh sebab itu, dibutuhkan sentuhan inovasi dalam pengelolaan sampah di TPA seperti yang dilakukan oleh Pengelola TPA Wisata Edukasi Talangagung, Kepanjen. Inovasi yang dilakukan oleh Ir. Koderi di TPA Wisata Edukasi Talangagung meliputi : pengendalian, penangkapan dan pemanfaatan biogas TPA dengan cara disalurkan kepada masyarakat sekitar. Dampak sosial lingkungan yang terjadi adalah gas beracun yang berbahaya bagi lingkungan seperti H2S, CO2 dan CH4 dapat hilangkan melalui sistem purifikasi. Sedangkan dampak ekonomi yang dirasakan adalah berkurangnya beban pengeluaran masyarakat untuk membeli gas LPG karena mendapatkan penyaluran gas langsung dari TPA. Dampak sosial yang terjadi adalah perubahan paradigma masyarakat yang enggan bahkan anti terhadap TPA, menjadi suka dengan adanya TPA disekitar mereka. Â  Kata kunci: pengelolaan sampah, inovasi, dampak inovasi